Full term newborns in non-nutritive suction evaluationand their relation on feeding performance - Yasmin Vieira Teixeira Alves; Jéssica Caroline de Jesus Santos; Ikaro Daniel de Carvalho Barreto; Cristina Ide Fujinaga; Andréa Monteiro Correia Medeiros
Abstract Objectives: To investigate full term newborns suction pattern in non-nutritive suction and their feeding performance. Methods: An analytical descriptive study was carried out from November 2016 to March 2017, with 50 dyads mothers/newborns through the non-nutritive suction evaluation and a direct observation on the newborn's performance on feeding. The data were distributed through simple and relative frequencies (percentages) when categorical or by mean, maximum, minimum and the standard deviation when is continuous, discrete or ordinal. To evaluate the mean differences, the Student's t test was used with significance level of 5%. Results: There were significant differences among the newborn's mandible movement ("newborn's mouth slightly open" p=0,005), suction ("cheek strain during feeding" p<0,001) and dyad mother and newborn positioning ("breasts supported with fingers on the areola" p=0,041 and baby's neck or trunk turned" p=0,041). Conclusions: Newborns that presented changes in their mandible movement on the Non-Nutritive Suction (NNS) also presented difficulties in feeding. The newborn's knowledge on suction pattern through the NNS has proven to be an important strategy that may help identify possible difficulties during feeding.